Quantitative magnetic resonance imaging parameters of lumbar paraspinal muscle impairment in myotonic dystrophy type 2 and their evolution with aging - Kokosova, Viktoria; Krkoska, Peter; Vlazna, Daniela; Sladeckova, Michaela; Dostal, Marek; Kerkovsky, Milos; Barusova, Tamara; Ovesna, Petra; Parmova, Olesja; Matulova, Katerina; Adamova, Blanka (Frontiers in neurology, 2025)
INTRODUCTION: Muscle magnetic resonance imaging (MRI) is an emerging method in the diagnosis and monitoring of muscular dystrophies. This cross-sectional, comparative study aimed to evaluate quantitative MRI (qMRI) parameters of the lumbar paraspinal muscles (LPM) in myotonic dystrophy type 2 (DM2), to assess their relationship with functional examination, and to evaluate their evolution with aging. METHODS: The study enrolled 37 DM2 patients and 90 healthy volunteers (HV) who were matched based on physiological parameters to create 35 pairs. Utilizing a 6-point Dixon gradient echo sequence MRI, fat fraction (FF), total muscle volume, and functional muscle volume (FMV) of the LPM and psoas muscle (PS) were obtained. Using correlation coefficients and regression models, the relationship between MRI and the maximal isometric lumbar extensor muscle strength (MILEMS) and lumbar extensor muscle endurance (LEME), and their evolution with age, were assessed. RESULTS: LPM showed significantly higher FF in DM2 patients compared to HV (21.3% vs. 11.3%, p-value <0.001). FMV of LPM correlated significantly with MILEMS (ρ = 0.5, p- value = 0.001) and FF with LEME (ρ = -0.49, p- value = 0.002) in DM2. No significant differences in the rate of deterioration in functional and morphological parameters of the LPM with age were observed between the two groups. CONCLUSION: We demonstrated morphological correlates of lumbar extensor muscle dysfunction in DM2 patients. The qMRI parameters of LPM correlated with functional parameters but could not be used either as a reliable biomarker of lumbar extensor muscle impairment or as a biomarker of disease progression.
Keywords: muscle strengh; paraspinal muscles; magnetic resonace imaging; endurance; myotonic dystrophy type 2